Fulfillment of raw material needs for soap production using the economic order quantity and safety stock - Oki Widhi Nugroho; Nicolas S. K. Telaumbanua; Tubagus Hedi Saepudin; Roberta Heni Anggit Tanisri (LPPMPK - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2023)
Soap Production Companies are faced with the problem of not fulfilling consumer demand which is characterized by a smaller actual number of shipments compared to the amount of consumer demand for this soap product. The management of the Soap Production Company identified that one of the causes of non-fulfillment of consumer demand was due to the production process being hampered by a shortage of production raw materials. Faced with the condition of increasingly high market demand, companies are constantly looking for ways to keep the supply of raw materials available in the right quantity and on time delivery. The calculation of ordering raw materials is carried out using the economist order quantity (EOQ) method and also the application of raw material safety stock. The EOQ method is applied to determine the order quantity and avoid large inventory costs. The amount of safety stock of raw materials is determined in anticipation of a shortage of raw materials during the production process. The amount of EOQ is obtained from the results of forecasting calculations and the value of the safety stock of raw materials obtained a value of 3.85% of the average raw material needs every month